2017
DOI: 10.18632/oncotarget.22171
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-216b sensitizes NSCLC cells to cisplatin-induced apoptosis by targeting c-Jun

Abstract: Platinum-based chemotherapy is still be the standard treatment for non-small cell lung cancer (NSCLC). Recently, studies demonstrate that some kinds of microRNAs (miRNAs) are associated with chemosensitivity of NSCLC cells to platinum-based treatment. Unfortunately, cancer cells usually change their expression profile of miRNAs to form drug resistance against chemotherapy. In the present study, we focused on miR-216b to investigate whether miR-216b determined sensitivity of NSCLC cells to cisplatin. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In cancer cells, cisplatin or other platinum-based drugs induces DNA damage which is an important apoptosis signal, 34 under the effect of cisplatin-dependent apoptosis signal, mitochondria-mediated intrinsic apoptosis pathway, which represents a collapse of mitochondria and activation of caspase-9 and caspase-3, 35,36 will be triggered. In the mitochondria apoptosis pathway, Bcl-2 and reactive oxygen species (ROS) are important regulators.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, cisplatin or other platinum-based drugs induces DNA damage which is an important apoptosis signal, 34 under the effect of cisplatin-dependent apoptosis signal, mitochondria-mediated intrinsic apoptosis pathway, which represents a collapse of mitochondria and activation of caspase-9 and caspase-3, 35,36 will be triggered. In the mitochondria apoptosis pathway, Bcl-2 and reactive oxygen species (ROS) are important regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that miR 647 overexpression led to decreased migration and invasion of SGC 7901/VCR cells (vincristine-resistant gastric cancer cells) by targeting ankyrin-B (ANK2), focal adhesion kinase (FAK), matrix metalloproteinase (MMP2 and MMP12), cluster of differentiation (CD44), and snail family transcriptional repressor 1 (SNAIL1) [ 21 ]. In addition, overexpression of miR-216b sensitizes non-small cell lung cancer cells to cisplatin-induced apoptosis by targeting c-Jun [ 22 ]. Restoring miR-27b levels was reported to enhance response to paclitaxel by directly targeting casitas B cell lymphoma-b and growth factor receptor-bound protein 2 in breast cancer [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, scientists have demonstrated that microRNAs modulate drug resistance in various cancers, including NSCLC . Overexpression of miR‐216b can sensitize NSCLC cells to cisplatin‐induced apoptosis by inhibiting c‐Jun . miR‐181c contributes to cisplatin resistance in NSCLC by targeting Wnt inhibition factor 1 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Overexpression of miR-216b can sensitize NSCLC cells to cisplatin-induced apoptosis by inhibiting c-Jun. 14 miR-181c contributes to cisplatin resistance in NSCLC by targeting Wnt inhibition factor 1. 15 In addition, miR-30a-5p can increase paclitaxel sensitivity in NSCLC through targeting BCL-2.…”
mentioning
confidence: 99%